1996
DOI: 10.1351/pac199668030613
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom-directed lithiations of chiral alkyl carbamates: A powerful tool for enantioselective synthesis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Stable structures of organolithium compounds are well-established as highly aggregated and strongly ligandassociated. [8,9,[29][30][31][32][33] The origin of the stabilization can be attributed to a favorable binding energy between the relatively concentrated positive charge of the small lithium atom and the negative charge of the carbanion or the electron pair of a Lewis base in intermolecular and/or intramolecular interactions. Support for lithium-electron pair complexation in ground states was provided by X-ray crystallographic structures.…”
Section: Methodsmentioning
confidence: 99%
“…Stable structures of organolithium compounds are well-established as highly aggregated and strongly ligandassociated. [8,9,[29][30][31][32][33] The origin of the stabilization can be attributed to a favorable binding energy between the relatively concentrated positive charge of the small lithium atom and the negative charge of the carbanion or the electron pair of a Lewis base in intermolecular and/or intramolecular interactions. Support for lithium-electron pair complexation in ground states was provided by X-ray crystallographic structures.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of the deprotonation of alkyl carbamates with n BuLi/(−)‐sparteine have established a strong preference for the abstraction of the pro‐ S proton followed by electrophilic substitution with retention of configuration 65. Thus, deprotonation of 57 is presumed to initially generate an S ‐configured organolithium compound, which epimerizes over time to the R complex, unless TMSCl is present.…”
Section: Chiral Organolithium Reagentsmentioning
confidence: 99%
“…The potassium ion is proposed to be coordinated by ligand 19 as well as the diketonate derived from 5a. 88 4 Michael Reactions The lupine alkaloid (-)-sparteine 22 was proved to be a powerful chiral additive for lithium-carbanionic chemistry [32]. Beak et al reported the conversion of benzylamines 21, deprotonated by nBuLi/(-)-sparteine, with dinitriles 23 (Scheme 4.10) [33].…”
Section: Miscellaneous Examplesmentioning
confidence: 99%